2012
DOI: 10.1002/jclp.21877
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Psychometric Properties of the Interpersonal Needs Questionnaire (INQ) Among Community‐Dwelling Older Adults

Abstract: Findings from this study support the use of the INQ-18 among community-dwelling older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 41 publications
6
48
0
2
Order By: Relevance
“…Further, they found convergent associations for the older adult sample between thwarted belongingness and both loneliness and social support, and convergent associations for perceived burdensomeness with both lower social worth and death ideation. Marty and colleagues (2012) also found support for the construct validity of the scale with older adults, including concurrent associations between both subscales and hopelessness, low meaning in life, and suicide ideation. These qualities establish the INQ’s potential as a valuable and useful tool in the domain of suicide research and prevention and indicate its relevance to late-life suicide.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Further, they found convergent associations for the older adult sample between thwarted belongingness and both loneliness and social support, and convergent associations for perceived burdensomeness with both lower social worth and death ideation. Marty and colleagues (2012) also found support for the construct validity of the scale with older adults, including concurrent associations between both subscales and hopelessness, low meaning in life, and suicide ideation. These qualities establish the INQ’s potential as a valuable and useful tool in the domain of suicide research and prevention and indicate its relevance to late-life suicide.…”
Section: Introductionmentioning
confidence: 70%
“…Previous research has found that scores derived from the INQ demonstrate good psychometric properties and construct validity, including a demonstrated prospective association with suicide ideation (Van Orden, Cukrowicz, Witte, & Joiner, 2012; Van Orden, Witte, Gordon, Bender, & Joiner, 2008). The construct validity of scores derived from the INQ has been demonstrated with older adults in two studies (Marty, Segal, Coolidge, & Klebe, 2012; Van Orden, Cukrowicz, Witte, & Joiner, 2012). Van Orden and colleagues (2012) found that the underlying latent structure of the INQ applied to both a younger adult sample and an older adult primary care sample.…”
Section: Introductionmentioning
confidence: 98%
“…There are several forms of the INQ that have been used in previous research, varying in the number of items included from an original pool of 25 items (Van Orden et al., ). In general, the various forms of the INQ have been found to have adequate to strong psychometric support for their use (e.g., the INQ‐12: Cukrowicz et al., ; Freedenthal, Lamis, Osman, Kahlo, & Gutierrez, ; Van Orden et al., ; the INQ‐18: Marty, Segal, Coolidge, & Klebe, ; Nsamenang, Webb, Cukrowicz, & Hirsch, ). The Perceived Burdensomeness subscale has been treated in past research as a stand‐alone measure of perceived burdensomeness (e.g., Cukrowicz et al., ); we treated it the same way in the current research to examine the validity of this type of use.…”
Section: Perceived Burdensomeness and Suicidementioning
confidence: 99%
“…Interpersonal Needs Questionnaire and has demonstrated a consistent significant association between perceived burdensomeness and suicidal ideation (e.g.,; Bryan, 2011;Freedenthal et al, 2011;Marty et al, 2012;Van Orden et al, 2009;Van Orden et al, 2012). Perceived burdensomeness has also been assessed via analysis of suicide notes by coding for burdensomeness-oriented cognitions.…”
Section: Most Empirical Research Examining Perceived Burdensomeness Hmentioning
confidence: 99%
“…Further evidence for the association between perceived burdensomeness and suicide-related behaviors has been reported in several studies. Since that time, correlations between perceived burdensomeness and suicidal ideation have been demonstrated among samples of young adults (Joiner et al, 2009), older adults Jahn, Cukrowicz, Linton, & Prabhu, 2011;Marty et al, 2012;Van Orden, Cukrowicz, Witte, & Joiner, 2012), college students of varying race and ethnicity Davidson et al, 2011;Davidson et al, 2009;Freedenthal et al, 2011;Lamis & Lester, 2012;Rasmussen, Slish, Wingate, Davidson, & Grant, 2012;Rasmussen & Wingate, 2011;Tucker et al, 2013;Van Orden, et al, 2012;Wong et al, 2011), American Indian/Alaskan Native adults (O'Keefe et al, 2014), military personnel (Bryan, Clemans, & Hernandez, 2012;Bryan, Cukrowics, et al, 2010;Bryan, Ray-Sannerud, et al, 2012), Spanish-speaking adult women (Garza & Pettit, 2010), and adolescents (Czyz et al, in press;Hill et al, in press;Merchant, 2010). Associations between perceived burdensomeness and a past suicide attempt have also been demonstrated in samples of military personnel (Bryan, Ray-Sannerud, et al, 2012;Monteith, Menefee, Pettit, Leopoulos, & Vincent, 2013) and clinical outpatients .…”
Section: Most Empirical Research Examining Perceived Burdensomeness Hmentioning
confidence: 99%